Efficacy Of Immunomodulatory Therapies In Neonatal Pemphigus A Randomized Controlled Trial - Mujoo, Sheetal (Journal of Neonatal Surgery, 2025)
Background: Neonatal pemphigus appears as a very uncommon autoimmune blistering condition which develops because maternal autoantibodies against desmosomal proteins pass through the placenta to the baby. The current available therapies do not provide satisfactory outcomes so medical scientists explore immunomodulatory treatments as safer and possibly better therapeutic options. Aim: The objective of this randomized controlled trial evaluated how well and safely immunomodulatory treatments worked for treating neonatal pemphigus. Materials and Methods: This clinical trial included 60 pemphigus-diagnosed newborns who were distributed randomly into two groups where the first group (n = 30) received IVIG and corticosteroids under immunomodulatory therapy and the second group (n = 30) received standard palliative care treatment. Results and discussion: The main evaluation target was blister duration but the study additionally analyzed judgments of disease seriousness alongside recurrence frequency and side effect occurrence. Eligible subjects in the immunomodulatory therapy group achieved blister cure more quickly (7.2 ± 1.8 days) than patients in the control group (12.5 ± 2.6 days, p < 0.001). Analysis revealed that the disease severity score reached 2.3 ± 0.8 points during week 2 in the immunotherapy group compared to 4.7 ± 1.2 points in the control group (p < 0.01). The recurrence rate between groups proved significant when compared with 10% versus 33% (p = 0.02). Complications between both patient groups proved comparable because no severe side effects occurred. Conclusion: Immunomodulatory therapy, particularly IVIG combined with corticosteroids, significantly improves clinical outcomes in neonatal pemphigus by accelerating blister healing and reducing disease severity without increasing adverse effects. These findings suggest that immunomodulatory therapy could be considered as a first-line treatment for neonatal pemphigus. Further long-term studies are required to confirm its sustained benefits and safety profile.